Effects of E-STREAM project-based learning with interactive e-modules on students’ critical thinking in environmental change - L. Lia; Evi Roviati; Ria Yulia Gloria; Maulani Pradiana (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Biology instruction in environmental change topics is still largely dominated by theoretical approaches, with limited integration of interdisciplinary learning frameworks. As a result, students have limited opportunities to develop critical thinking skills through contextual and project-based learning experiences.  Objectives: This study aimed to examine the effectiveness of E-STREAM (Environmental, Science, Technology, Religion, Engineering, Arts, and Mathematics)–based learning supported by e-modules in enhancing students’ critical thinking skills on environmental change topics. Methods: A quasi-experimental method with a non-equivalent control group design was employed, involving 68 tenth-grade students at MAN 3 Cirebon. The experimental group received E-STREAM-based e-module instruction through Project-Based Learning, while the control group received conventional instruction. Data were collected using critical thinking tests, observation sheets, and student response questionnaires. Test data were analyzed using N-Gain and an independent-samples t-test, while the remaining data were analyzed descriptively. Results: The findings indicated that the experimental group achieved a higher level of improvement in critical thinking skills (N-Gain = 0.78) compared to the control group (0.72). Furthermore, the independent sample t-test revealed a statistically significant difference between the two groups (p = .004). Conclusion: E-STREAM-based learning with e-modules significantly improved students’ critical thinking skills compared with conventional biology instruction.